Impact of cyberattacks on stock performance: a comparative study. (12th November 2018) - Tweneboah-Kodua, Samuel; Atsu, Francis; Buchanan, William
Abstract : Purpose: The study uses cyberattacks announcements on 96 firms that are listed on S&P 500 over the period from January 03, 2013, to December 29, 2017. Design/methodology/approach: The empirical analysis was performed in two ways: cross-section and industry level. The authors use statistical tests that account for the effects of cross-section correlation in returns, returns series correlation, volatility changes and skewness in the returns. Findings: These imply that studying the cumulative effects of cyberattacks on prices of listed firms without grouping them into the various sectors may be non-informative; financial sector firms tend to react cumulatively to cyberattacks over a three-day period than other sectors; and technology firms tend to be less reactive to the announcement of a data breach. Such firms may possibly have the necessary tools and techniques to address large-scale cyberattacks. Research limitations/implications: For cross-section analysis, the outcome shows that the market does not significantly react to cyberattacks for all the event windows, except [−30, 30], while for the sector-level analysis, the analysis offers two main results. Practical implications: First, while there is a firm reaction to cyberattacks for long event window for retail sector, there is no evidence of a cumulative firm reaction to cyberattacks for both short and long event windows for the industrial, information technology and health sectors. Second, the firms in the financial sector, there is a strong evidence of cumulative reaction to cyberattacks for [−1, 1] for the financial industry, and the reactions disappear for relatively longer event windows. Social implications: These imply that studying the cumulative effects of cyberattacks on prices of listed firms without grouping them into the various sectors may be non-informative, the financial sector firms tend to react cumulatively to cyberattacks over a three-day period than other sectors, technology firms tend to be less reactive to the announcement of a data breach, possibly such firms may have the necessary tools and techniques to address large-scale cyberattacks. Originality/value: The work provides new insights into the effect of cyber security on stock prices.